Latihan Auditori Pada Anak dengan Gangguan Pendengaran: Studi Kasus Tunggal - Alamsyah, Deni; Ramadhanti, Nadifa; Rahman, Ricky; Purnomo, Bayu (Akademi Terapi Wicara, 2023)
verbal communication is studied primarily through the auditory modality. Adverse impact on language development, cognition, academics, including verbal communication when there is a decrease in hearing sensitivity. Hearing loss will result in a reduced ability to understand and produce intelligible speech.